Faktor-Faktor Yang Berhubungan Dengan Obesitas Pada Siswa/i Kelas VII Dan VIII Di SMP Negeri 34 Medan Tahun 2014 - Ratu Afrienny; Rahayu Lubis; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Obesity is a condition where a person has a weight heavier than their ideal weight because of a build up of fat in his body. SUSENAS 2004 data show that obesity in children has reached 11%. The purpose of this study was to determine the factors associated with obesity in children SMP 34 Medan in 2014This research is an observational anality with cross sectional approach. Sample of 100 students were taken by purposive sampling. The research instrument used was a questionnaire as well as the scales of measuring instruments gauges, direct observation. Univariate data were analyzed descriptively and bivariate data were analyzed using the chi square test with 95% CI.The results were obtained proportion of obesity prevalence in SMP 34 field as much as 56%. The highest proportion of respondents were in the age 11-13 years (69%), female gender (62%), Batak tribe (40%), Islam (94%), self-employed parents (68%), the pattern of unhealthy lifestyle (51%), not excess eating (65%), light activity (72%), there was no family history (68%) and high economic status (80%). Bivariate results indicate a significant relationship between age (p = 0.014), physical activity (p = 0.035) and family history (p = 0.002) with the incidence of obesity.It is suggested to student of SMP Negeri 34 Medan who are obese to maintain a healthy lifestyle and increasing physical activity in order to minimize risks associated with obesity later in life.Keywords: Obesity, Age, fisic activity, family history